2008
DOI: 10.1016/j.peptides.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A derivative of the melanocortin receptor antagonist SHU9119 (PG932) increases food intake when administered peripherally

Abstract: Melanocortin receptors are considered promising candidates for the treatment of behavioral and metabolic disorders ranging from obesity to anorexia and cachexia. These experiments examined the response of mice to peripheral injections of two compounds. PG932 is a derivative of SHU9119 which is non-selective antagonist of melanocortin-3 and melanocortin-4 receptors (Mc3r, Mc4r). PG946 is a derivative of a hybrid of alpha-and beta-MSH, and is a moderately selective Mc3r antagonist. SHU9119 increases food intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…In vivo structure:activity studies were modeled around an established anticachexia MC4R antagonist peptide that had apparent BBB transport activity; PG932 (Table 1). We noted that PG932's structure included two dipeptide features that differentiated it from an analogous MC4R antagonist peptide (SHU9119) that lacked BBB transport (Sutton et al, 2008). These included a proline (adjacent to an aromatic residue) within the cyclized region of the sequence, and a C-terminus composed of non-polar residues from the flanking region of α-MSH; Pro-Val (Eberle and Schwyzer, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo structure:activity studies were modeled around an established anticachexia MC4R antagonist peptide that had apparent BBB transport activity; PG932 (Table 1). We noted that PG932's structure included two dipeptide features that differentiated it from an analogous MC4R antagonist peptide (SHU9119) that lacked BBB transport (Sutton et al, 2008). These included a proline (adjacent to an aromatic residue) within the cyclized region of the sequence, and a C-terminus composed of non-polar residues from the flanking region of α-MSH; Pro-Val (Eberle and Schwyzer, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The MC antagonist pharmacophore in TCMCB03 (His-D-Nal-Arg-Trp) is identical to that in SHU9119, an established MC4R antagonist. However, SHU9119 has no transport activity, requiring intracerebroventricular administration for use as an anticachexia agent (Sutton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 ) and also an MC3/4R antagonist, stimulates food intake when administered peripherally, and that this action is dependent on MC4Rs. 191 Navarro et al observed what appeared to be a stimulatory effect of MTII administered icv. to Mc4r −/− mice, while the inhibitory effects of peripherally administered MTII were retained.…”
Section: Melanocortin-3 Receptors In Metabolic Homeostasismentioning
confidence: 97%
“…NPY/AgRP and Pomc/CART neurons may transmit signals of energy status into the DMH expressing melanocortin-3 receptor (Mc3r). Alternatively, neurons expressing Mc3r reside in other areas of the brain, such as the LHA and ventral tegmental area (102), involved in complex behavioural processes. An involvement of these neurons in the expression of rhythms in arousal and food-seeking behaviour is also possible.…”
Section: Neuroanatomy and Molecular Composition Of The Mammalian Biolmentioning
confidence: 99%